Socio-religious functions of three Theban festivals in the New Kingdom: the festivals of Opet, the Valley, and the New Year - Fukaya, M (2014)
In addition to temple rituals performed for the god by the king, festivals incorporated a broader domain, where a wider public had access to the divine. The participants in feasts ranged from the royal, officials and priests to the non-elite and the dead. Theoretically and ideologically, individuals would have received fruits of the divine power through the king by taking part in celebrations to variable extent. This functioned a vehicle for the god and the king to maintain their authoritative credibility and, by extension, the world order. The circulation of the divine force formed a different appearance at each festival, such as material supplies, promotions, and juridical decrees. These divine conveyances would have more or less met people’s social and religious needs. By embracing modality, periodicity, and publicness, festivals provided participants and audiences with a public setting and a formal means, whereby they were able to seek their identity as part of society. This may or may not have been relevant to personal piety, allegiance, responsibilities, and goodness, but public celebrations at least brought the king’s subjects together to common grounds for official beliefs and social decorum. In order to demonstrate such socio-religious functions of festivals, I will attempt to focus on and examine three Theban celebrations in the New Kingdom, namely, the Festivals of Opet, the Valley, and the New Year, about which a wealth of information has survived. The examination can hardly be possible without exploring the history of these feasts because their development from earlier times, to which part of this thesis is also devoted, shows the continuity of elements essential to Egyptian cult practices, particularly those associated with the mortuary cult.